A study on dioscorea esculenta starch as a binder for tablets - Basco, Ma. Eilyn F.
The usefulness and effects of using starch from native yams called Dioscorea esculenta (Lour.) Burkill (Fam. Dioscoreaceae) or tugi is shown by the small amount of tugi within the desired range of hardness.